The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1039/a605548f
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthesis of trans-Iodohydrins using Iodine–Cerium(IV) Salts†

Abstract: The reaction of cycloalkene with iodine-cerium(IV) ammonium nitrate (CAN) in acetonitrile-water (10 :1-1:1) affords the corresponding trans-iodohydrins and trans-iodonitrates; when iodine-cerium(IV) sulfate (CS) in acetonitrile-water (10 :1) at 50 °C is used, trans-iodohydrins are obtained preferentially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…Analytical data for compounds 2 g, [29] Procedure for the preparation of 2 d: HBF 4 (4.1 mL of 35 % aqueous solution, 4 equiv, 20 mmol) and H 2 O 2 (2 mL, 4 equiv, 20 mmol, 33 % aqueous solution) were used. Analytical data for compound 2 d [26] were in complete accordance with literature values.…”
Section: Methodsmentioning
confidence: 99%
“…Analytical data for compounds 2 g, [29] Procedure for the preparation of 2 d: HBF 4 (4.1 mL of 35 % aqueous solution, 4 equiv, 20 mmol) and H 2 O 2 (2 mL, 4 equiv, 20 mmol, 33 % aqueous solution) were used. Analytical data for compound 2 d [26] were in complete accordance with literature values.…”
Section: Methodsmentioning
confidence: 99%
“…The products were known and identified by 1 H-NMR, 13 C-NMR and GC-MS spectra by reference to the literature. Since the reference of 2-acetoxy-4-hexanone (6) was not found, the spectral data of 6 are shown below. …”
Section: Typical Proceduresmentioning
confidence: 99%
“…Cerium(IV) salt has been utilized extensively for a variety of oxidative transformations. In the previous papers, we reported a synthesis of trans-iodohydrins from cycloalkenes using iodine-ammonium cerium(IV) nitrate (CAN) or CS, 6 the oxidative cleavage of 2-alkyl substituted cycloalkanones using CS in alcohols and acetic acid, 7 a synthesis of carboxylic esters from alkenes using CS in carboxylic acids, 8 a new onepot synthesis of 3-acylisoxazoles using CAN, 9,10 a synthesis of 2-oxo-and 2-oxo-5-hydroxy derivatives using CS in carbonyl compounds-H 2 O 11 and reaction of α,β-unsaturated ketones with cerium(IV) salts in alcohols. 12 In this paper we report that the reaction of α,β-unsaturated ketones with CS in acetic acid gave the corresponding β-acetoxy ketones.…”
Section: Introductionmentioning
confidence: 99%
“…66 Asakura et al have reported the bromination of C-5 of uracil nucleosides using CAN and lithium bromide in MeCN. In this reaction, they have used stoichiometric amounts of CAN and lithium bromide.…”
Section: Scheme 32mentioning
confidence: 99%